2012
DOI: 10.1021/jf302505y
|View full text |Cite
|
Sign up to set email alerts
|

Spectral Changes of Atlantic Salmon (Salmo salar L.) Muscle during Cold Storage As Affected by the Oxidation State of Heme

Abstract: The spectra of fresh salmon fillets change due to storage and packaging atmospheres. The aim of this study was to demonstrate the effects of heme oxidation states on spectral development in salmon fillets and to investigate the origin of a shoulder peak representing important spectral variations during storage. Hyperspectral images of fresh salmon fillets and mince with various water contents were collected during storage under different atmospheres. In addition, the absorption spectra of extracted salmon hemo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
9
0

Year Published

2013
2013
2019
2019

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 8 publications
(9 citation statements)
references
References 49 publications
0
9
0
Order By: Relevance
“…Treatments with different concentrations of grape skin and seed extracts showed similar mesophilic count and reached the limit of 7.0 CFU/g after 3 days of storage (Ojagh, Rezaei, Razavi, & Hosseini, ; Tenore et al, ). A research developed with salmon fillets (Sone, Olsen, & Heia, ) showed air‐stored samples suffering extensive microbial growth reaching 8.0 log CFU g −1 after day 8 in the storage experiment. The difference regarding shelf life could be due to higher initial mesophilic count in the present experiment.…”
Section: Discussionmentioning
confidence: 99%
“…Treatments with different concentrations of grape skin and seed extracts showed similar mesophilic count and reached the limit of 7.0 CFU/g after 3 days of storage (Ojagh, Rezaei, Razavi, & Hosseini, ; Tenore et al, ). A research developed with salmon fillets (Sone, Olsen, & Heia, ) showed air‐stored samples suffering extensive microbial growth reaching 8.0 log CFU g −1 after day 8 in the storage experiment. The difference regarding shelf life could be due to higher initial mesophilic count in the present experiment.…”
Section: Discussionmentioning
confidence: 99%
“…Hyperspectral imaging technique, as an innovative and emerging tool, combines traditional spectroscopy and digital imaging or computer vision (Sun ; Wang and Sun ; Sun and Brosna ; Jackman and others ; Costa and others ) to acquire both spectral and spatial information from the object (Mathiassen and others ; Elmasry and others ; Sone and others ; Huang and others ). Figure shows the common steps of hyperspectral imaging for the detection of food quality.…”
Section: Applications Of Hyperspectral Imagingmentioning
confidence: 99%
“…Oxidative rancidity is an important organoleptic characteristic regarding the rejection or approval of fish, second only to microbiological changes . The shelf life of fresh salmon storage at 1°C is approximately 8 days, because enzymatic and chemical reactions are usually responsible for the initial loss of freshness, while microbial activity is responsible for deterioration …”
Section: Introductionmentioning
confidence: 99%
“…Packaging technologies have been developed for fresh fish and fishery products to control and prolong their shelf life (modified atmosphere packaging or vacuum packaging) . Antioxidant films are also alternatives to reduce or minimize oxidative deterioration during storage .…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation